1987
DOI: 10.1902/jop.1987.58.11.747
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Detection of Dental Calculus

Abstract: To determine the sensitivity and specificity of the radiographic detection of calculus, 275 proximal tooth surfaces from 18 patients were evaluated. Standardized periapical radiographs obtained before extraction were coded, batch processed, and evaluated independently by two investigators under optimum viewing conditions. After extraction, the teeth were photographed and evaluated both microscopically and by planimetry on 40 X linear projections. Evaluation of calculus by conventional radiography showed low se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
2
5
2
Order By: Relevance
“…Buchanan et al's sensitivity and specificity of 43.8% and 92% compare favorably to the 50% and 82.2% in the present study, yet there were significant differences in predictive value. Buchanan et al 12 reported PPV and NPV of 71.7% and 74.6%, compared with 94% and 23.2% in the current study. This difference may be due to the greater prevalence of calculus positive surfaces in our sample (83.6% versus 55.6%), for it is known that an increase in the prevalence of the variable of interest corresponds to an increase in PPV and decrease in NPV.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Buchanan et al's sensitivity and specificity of 43.8% and 92% compare favorably to the 50% and 82.2% in the present study, yet there were significant differences in predictive value. Buchanan et al 12 reported PPV and NPV of 71.7% and 74.6%, compared with 94% and 23.2% in the current study. This difference may be due to the greater prevalence of calculus positive surfaces in our sample (83.6% versus 55.6%), for it is known that an increase in the prevalence of the variable of interest corresponds to an increase in PPV and decrease in NPV.…”
Section: Discussioncontrasting
confidence: 56%
“…A sharp explorer * was used under 2.5x magnification † to detect calculus on dried interproximal surfaces by a single examiner (JH). Similar to Buchanan et al, 12 each interproximal surface was scored with a numerical designation based on the size of the largest calculus deposit: (0) no calculus present, (1) smooth, flat deposit of different color than the root surface, (2) smooth-to-irregular deposit of different color than the root surface and tactile step height <0.5 mm, and (3) rough deposit of different color than the root surface and tactile step height of at least 0.5 mm. Teeth were positioned with interproximal surfaces parallel to the bench surface and stabilized onto a labeled index card using rope wax.…”
Section: Clinical Protocolsupporting
confidence: 65%
See 1 more Smart Citation
“…Calculus on interproximal surfaces may be detected by periodontal probe and more accurately by intra-oral periapical radiographs, although the accuracy of detection depends on radiographic projections [11] . The superior periapical radiographs can only detect 43.8% of the proximal surfaces that is verified visually after extraction [12] . Advanced technologies, including dental endoscopes [13] , fiber-optic probes [14] , autofluorescence [15] , and lasers [16] , are being used recently to better detect subgingival calculus.…”
Section: Introductionmentioning
confidence: 99%
“…Dental calculus on interproximal surfaces may be revealed by radiographs, although the sensitivity of detection differs between radiographic projections [11]. While periapical radiographs are superior to other radiographs in identifying calculus, they only detect 43.8% of the proximal surfaces where deposits were verified visually after extraction [12]. Advanced technologies, including dental endoscopes [13], fiber-optic probes [14], autofluorescence [15], and lasers [16], have been introduced to better detect subgingival calculus.…”
Section: Introductionmentioning
confidence: 99%